THE INFLUENCE OF COMPENSATION ON EMPLOYEES' PRODUCTIVITY AT UNIVERSITAS KRISTEN INDONESIA PAULUS - Jane Lintang (Entrepreneurship Undergraduate Program at Amkop Business School, 2023)
This research aims to determine the effect of compensation on employee productivity at the Indonesian Christian University Paulus. This research was conducted at the Indonesian Christian University Paulus using quantitative research methods. The number of samples taken was 149 employees at UKIP Makassar. As a data collection technique, a questionnaire was used, then the data was processed using the SPSS Version 25 application. After the data was processed and analyzed, it was found that Compensation (X) had a positive but not significant effect on Employee Productivity (Y). For this reason, the author suggests that the leaders and foundations of UKIP Makassar can increase allowances for their employees to improve performance, as well as pay more attention to attendance issues in order to increase employee productivity. Keywords: Compensation, Productivity, Employees, UKIP, Makassar